Pembelajaran Berbasis Proyek Menggunakan Senam Transformasi dan Tetris Geogebra untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Muhammad Abror (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
The ability to think creatively is an important ability in mathematics to deal with the demands of the 21st century. One learning model that can improve students' mathematical creative thinking skills is Project Based Learning. This study aims to determine the improvement of students' mathematical creative thinking abilities through Project Based Learning using Transformation Gymnastics and Tetris GeoGebra. Research instruments used in this study is a test in the form of description, consisting of pretest and posttest that measures the ability of mathematical creative thinking including fluency, flexibility, originality, and elaboration. Data analysis includes tests of normality, homogeneity, and t-test using SPSS application assistance. The results showed that there was a significant increase in the value of students' creative thinking abilities, both in classrooms with Project Based Learning using Transformation Gymnastics and in classrooms with Project Based Learning using Tetris GeoGebra. There was no significant difference between the average posttest in the two classes. Thus, the two project tasks used in this Project Based Learning can be used in learning Transformation material.